2010
DOI: 10.4111/kju.2010.51.12.843
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Male Overactive Bladder with Intravesical Prostatic Protrusion

Abstract: PurposeMale overactive bladder (OAB) may be caused by prostatic pathologies such as bladder outlet obstruction (BOO). Intravesical prostatic protrusion (IPP) has been found to correlate with BOO and acute urinary retention. We investigated the interrelation between male OAB symptoms and IPP for estimating anatomical changes to the prostate.Materials and MethodsWe assessed 179 consecutive men aged >40 years who presented with lower urinary tract symptoms. The initial evaluation included International Prostate S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 17 publications
2
19
0
2
Order By: Relevance
“…The underlying mechanisms by which IPPL affects urinary continence recovery after LRP remains unclear, but some hypotheses have been proposed. IPPL was initially known as a better predictor of bladder outlet obstruction and overactive bladder compared with prostate volume [15,16]. In our series, patients with intravesical prostatic protrusion had a significant proportion of treatment for LUTS.…”
Section: Resultsmentioning
confidence: 74%
“…The underlying mechanisms by which IPPL affects urinary continence recovery after LRP remains unclear, but some hypotheses have been proposed. IPPL was initially known as a better predictor of bladder outlet obstruction and overactive bladder compared with prostate volume [15,16]. In our series, patients with intravesical prostatic protrusion had a significant proportion of treatment for LUTS.…”
Section: Resultsmentioning
confidence: 74%
“…In the present study, IPP grade was strongly correlated with total IPSS as well as storage subscale score, but was weakly correlated with voiding subscale score. Similarly, Kim and Kim reported that prevalence of male OAB was higher in the IPP group than in the non‐IPP group 2 . These results suggest that IPP might induce storage symptoms by irritating and extending the bladder neck and trigone as well as voiding symptoms by BOO.…”
Section: Discussionmentioning
confidence: 72%
“…Similarly, Kim and Kim reported that prevalence of male OAB was higher in the IPP group than in the non-IPP group. 2 These results suggest that IPP might induce storage symptoms by irritating and extending the bladder neck and trigone as well as voiding symptoms by BOO.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations